A state-of-the-art review of the modes and effectiveness of multimedia input for second and foreign language learning. Issue 9 (8th December 2022) - Zhang, Ruofei; Zou, Di
Abstract: Multimedia technology has been advancing the development of second/foreign language learning over the past two decades. Multimedia input (e.g. text, images, audio, animation, and captions/subtitles) has been extensively investigated and applied as facilitative in second/foreign language education. The increasing recognition and application appear to call for a review of the studies investigating the effectiveness of various multimedia input modes for promoting second/foreign language learning to provide a contemporary and comprehensive picture of the field. Accordingly, the present study reviews 41 relevant articles appearing in SSCI journals while identifying five main types of tools used in the studies (i.e. computers, mobile devices, printed materials, audio players, and the integration of PowerPoint slides and stereo speakers) and four main target aspects (i.e. vocabulary knowledge, listening comprehension, reading comprehension, and grammar knowledge). Reported most frequently were the effectiveness of three features: audio-plus-animation-plus-captions/subtitles in developing vocabulary and grammar knowledge; audio-plus-animation in promoting listening comprehension; and text-plus-audio in facilitating reading comprehension. The reviewed articles collectively noted the need for more research on learner factors and influences of different features of multimedia input on learning outcomes and learning process.